Agropreneurship empowerment: The application of digitalization in local MSMEs “Tujuh Bersaudara”, Karang Tengah Village - Awa; Yulianingsih; Ismartaya; Marathuzzahrah; Ramadani, Fuji Tri; Mahmudah, Mariam; Nenah (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This Community Service Program (PkM) in Karang Tengah Village aimed to empower local MSMEs, especially “Tujuh Bersaudara” MSMEs, by applying digitalization in agropreneurship to address real business challenges. Method: The program was implemented through five stages: observation, interviews, discussions, data analysis, and execution in the form of training, mentoring, and facilitation. Practical Applications: The initiative improved MSMEs identity through professional logos, trademarks, and packaging, while marketing capacity was strengthened via social media, online marketplaces, and digital strategies. In finance, MSMEs acquired knowledge of simple bookkeeping, production cost analysis, and cost of goods sold determination. Legal credibility was enhanced through the acquisition of Business Identification Numbers (NIB), enabling access to government support. Conclusion: The PkM program strengthened MSMEs capacity and competitiveness while fostering social cohesion and solidarity in Karang Tengah Village, generating both economic and social impact.